The Role of the Academic Librarian in the Sciences of Food and Health. Issue 3 (3rd July 2019) - Korjonen, Maria Helena; Barratt, Caroline C.
ABSTRACT: This study investigates the information seeking behavior of faculty and graduate students in the sciences of food and health. We compare three food science research sources through quantitative and qualitative research methods of interviews, observational studies, and surveys. We aimed to discover what motivates scientists' information seeking, how they search, what barriers they experience, and how they critically evaluate information sources. We explored faculty perceptions of literature review practice in the field and by their students, their preferences for training and best practice in order to improve research quality. Recommendations for librarians supporting food science and related departments are provided.